The Hunter and the Farmer: Jean Toomer’s Depression-Era Masculinist Writings (AmeriQuests, 2008)
In 1937, after he had written the novel Cane, left the African-American culture of Harlem, studied under the mystic Georges Gurdjieff in France, lost his wife to childbirth, and married for the second time, Jean Toomer sought to publish a series of essays. The subjects varied, but the most common theme was masculinity—men’s prerogatives, natures, and responsibilities. He theorized women’s temperaments as well, but it was clearly the study of maleness that captured his attention. Toomer’s interest was noteworthy given the fact that he became ever more concerned with sexuality and gender as he left behind his African-American identity. Toomer did not intend to “pass,” as is commonly assumed—he actually wanted to be raceless, or of the “American” race. In his adopted home in the Pennsylvania countryside, Toomer attempted to construct his life based entirely on his masculinity. In Toomer’s opinion, his entire household-- his white wife, his light-skinned daughter, and various temporary occupants—was a social experiment in supporting his masculine genius and creativity. This essay is an intellectual history of Toomer’s self-construction. Using his diaries and published and unpublished writings, I will explain how Toomer saw his own male identity and how, although he had renounced his blackness, his racial identity mediated his ideal of his gender.